An Analysis of Apology Strategies Used by Characters in Inside Out Movie - Farhan, Wildan; Pradipta, Bramantya (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
Apology is crucial in communication for maintaining social harmony and resolving conflicts. This research examines apology strategies used by characters in the 2016 Oscar-winning animated movie